Educação sexual na escola - concepções e práticas - Oliveira, Célia Maria Soares de (2006)
The present study is a qualitative case study research, which aims to analyze the pedagogic practice of sexual education in two schools of elementary teaching in Floriano, state of Piauí. The selection of the schools was done by the following criteria: one school must be a public school and the other one must be a private school; both of them must be elementary teaching schools, teaching from 5th to 8th grade, with morning and/or afternoon sessions; both schools must have a sexual education teacher in its staff in addition to the Science teacher. Teachers and students were interviewed with the intention to characterize better the educational practice. Through this study it is possible to conclude that the researched schools develop two main kind of sexual education: an occult one and an explicit one, with medical, pedagogic and politic approaches. The teachers show maturity and understanding about their limitations and possibilities of realizing sexual education as an educational practice of the school. Besides, they conceive the school as the perfect place for that pedagogic exercise. However, they agree that only properly qualified people should exercise it. For the students, sexual education is important and necessary for making them reflect about it. Nevertheless, the lack of integration and systematization of the approached contents, among other factors, makes sexual education happens in a still fragile way in the studied reality. As the main characters of that reality, the students themselves suggested what sexual education they would like to have at school. Yet, it is up to the teachers to ponder about the institutional possibilities of the school and to think over the bureaucratic process perceiving it as a capital force of the unit and, therefore, a political and not only functional subject.